Elizabeth Occupies Wall Street - Davis, Mike (Social justice, 2012)
A personal narrative is presented which explores the author's experience of working with social activist Elizabeth "Betita" Sutherland Martínez when she was organizing the Friends of Student Nonviolent Coordinating Committee in New York City in 1964.